2019
DOI: 10.1038/s41598-019-44662-w
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Toothbrushing and Behavioral Risk Factors of Non-communicable Diseases: A population Based Survey of 4500 adults in China

Abstract: Non-communicable Disease (NCD) related behavioral risk factors (BRF) plays a crucial role in NCD prevention, as does oral hygiene behavior in oral health promotion. We examined the association between NCD BRF and toothbrushing using data from a population-based survey, which recruited 4485 adults aged 18+ years, in Chongqing city, China. Prevalence of five NDC BRF and their clustering within individual were determined by toothbrushing frequency. Ordinal logistic regression examined the association between toot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…First, diet quality, such as total energy intake and vegetable and fruit intake, was not investigated, although eating habits were included in our study. It has been reported that toothbrushing frequency is positively associated with intake of vegetables and fruits, 36 which contributes to the prevention of metabolic abnormalities. 37 We also did not investigate inflammatory parameters, such as highsensitivity C-reactive protein, which is considered to be responsible for the link between gingival and systemic inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…First, diet quality, such as total energy intake and vegetable and fruit intake, was not investigated, although eating habits were included in our study. It has been reported that toothbrushing frequency is positively associated with intake of vegetables and fruits, 36 which contributes to the prevention of metabolic abnormalities. 37 We also did not investigate inflammatory parameters, such as highsensitivity C-reactive protein, which is considered to be responsible for the link between gingival and systemic inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…These impacts can take the form of pain, discomfort, lower self‐esteem, and poor school attendance and performance [1–3]. One of the main indicators for oral hygiene is tooth‐brushing frequency [4]. Regular tooth‐brushing habits adopted in adolescence are usually sustained into adulthood and may reduce the burden of disease, as they may have a protective role against cardio‐metabolic risk factors [5, 6].…”
Section: Introductionmentioning
confidence: 99%
“…Tooth‐brushing habits are enmeshed in complex daily habits and can indicate the wider context of adolescents’ lifestyles [8, 10, 19]. The association between tooth‐brushing frequency and elements of lifestyle, such as dietary behaviour, physical activity, sedentary behaviour, nutritional status, smoking, and alcohol and cannabis use, have been demonstrated [4, 15, 20–24]. It has been suggested that lifestyle might reflect the health consciousness and personal characteristics of a person and is also associated with psychosocial factors shaped by the local cultures and shared contexts [11, 25–28].…”
Section: Introductionmentioning
confidence: 99%